Paclitaxel Nanomedicines: Molecular Mechanisms of Drug Resistance, Tumor Microenvironment-Responsive Delivery, and Translational Challenges - Dejun Cheng; Guowei Yang; Ruibin Kong; Qin Liu; Li Li; Yunpeng Luan; Qijiang Shu (International Journal of Molecular Sciences, 2026)
Paclitaxel (PTX) remains a major component of treatment for solid tumors, but its clinical performance is limited by poor aqueous solubility, solvent-associated toxicity, heterogeneous tumor exposure, and multifactorial drug resistance. This narrative review examines PTX nanomedicines from a molecular pharmacology perspective, focusing on how carrier design interacts with resistance pathways, tumor microenvironment signals, and intracellular drug trafficking. We outline resistance mechanisms involving ATP-binding cassette subfamily B member 1 (ABCB1)/P-glycoprotein (P-gp)-mediated efflux, microtubule remodeling, apoptosis-related signaling, epigenetic regulation, extracellular matrix deposition, hypoxia, and redox imbalance. We evaluate albumin-bound formulations, liposomes, polymeric micelles, stimuli-responsive carriers, biomimetic systems, carrier-free prodrug assemblies, and multidrug co-delivery platforms according to the molecular and biological barriers they address. Particular attention is given to pH-, redox-, enzyme-, and hypoxia-responsive release; tissue penetration and subcellular localization; and co-delivery of PTX with chemosensitizers, nucleic acids, or pathway-directed agents. Molecular simulation and machine learning are considered as tools for formulation optimization and biomarker-guided patient stratification. These approaches can coordinate drug exposure and resistance modulation in preclinical models, but clinical benefits remain inconsistent. Translation will require reproducible formulations, clinically predictive models, direct measurement of intratumoral drug levels, and validated biomarkers linking molecular delivery mechanisms to patient outcomes.